The Relationship between Knowledge Management and Compensation and Employee Performance at the Regional Revenue Management Agency of Morowali Regency - Daud, Salma; Armawati, Armawati (CV. Publikasi Indonesia, 2025)
One of the factors that affect performance is knowledge management and compensation. There needs to be great attention to the management process of knowledge management and compensation. This study aims to analyze the influence of performance influenced by knowledge management and compensation on the Morowali Regency Regional Revenue Management Agency. The number of samples used was 87 people with a quantitative research type. Data collection techniques are literature studies, observations and questionnaires. The analysis technique used multiple linear regression using SPSS software version 26. The results of this study show that simultaneously and partially, the variables of knowledge management and compensation have a positive and significant effect on employee performance at the Morowali Regency Regional Management and Revenue Agency.